An In Vitro Assessment of Gutta-Percha Coating of New Carrier-Based Root Canal Fillings - Raghad Abdulrazzaq Alhashimi; Richard Foxton; Shihab Romeed; Sanjukta Deb (The Scientific World Journal)
The first aim of this paper was to evaluate the push-out bond strength of the gutta-percha coating of Thermafil and GuttaCore and compare it with that of gutta-percha used to coat an experimental hydroxyapatite/polyethylene (HA/PE) obturator. The second aim was to assess the thickness of gutta-percha around the carriers of GuttaCore and HA/PE obturators using microcomputed tomography (μCT). Ten (size 30) 1 mm thick samples of each group (Thermafil, GuttaCore, and HA/PE) were prepared. An orthodontic wire with a diameter of 0.5 mm was attached to the plunger of an Instron machine in order to allow the push-out testing of the gutta-percha coating. Five samples of (GuttaCore and HA/PE) were scanned using μCT. The data obtained were analysed with one-way analysis of variance and Tukey post hoc test. HA/PE obturators exhibited significantly higher push-out bond strength (P<0.001) determined at 6.84 ± 0.96 than those of Guttacore around 3.75 ± 0.75 and Thermafil at 1.5 ± 0.63. GuttaCore demonstrated significantly higher bond strength than Thermafil (P<0.001). μCT imaging revealed that the thickness of gutta-percha around the experimental HA/PE carrier was homogeneously distributed. The bondability and thickness of gutta-percha coating around HA/PE carriers were superior to those of GuttaCore and Thermafil obturators.